Dominant role of winds near Sri Lanka in driving seasonal sea level variations along the west coast of India. Issue 13 (2nd July 2016) - Suresh, I.; Vialard, J.; Izumo, T.; Lengaigne, M.; Han, W.; McCreary, J.; Muraleedharan, P. M.
Abstract: The strong seasonal cycle of sea level along the west coast of India (WCI) has important consequences for ecosystem and fisheries, and the Lakshadweep high/low in the southeast Arabian Sea is important for fisheries and the Indian summer monsoon. Previous studies suggested that WCI sea level variability is primarily driven by remote wind forcing from the Bay of Bengal and equatorial Indian Ocean through coastal Kelvin wave propagation. Using a linear ocean model, we demonstrate that wind forcing in a relatively small region around the southern tip of India and east of Sri Lanka contribute to ~60% of this variability. Wind variations from the rest of the Bay and the equator only account respectively for ~20% and ~10%. Sea level signals forced by the "southern tip" winds extend westward into the eastern Arabian Sea through Rossby wave propagation, with more than 50% contribution in the Lakshadweep high/low region. Key Points: Winds near Sri Lanka drive 60% of Indian west coast seasonal sea level Bay of Bengal wind forcing contributes to only 20% Winds near Sri Lanka are also essential for driving Lakshadweep high/low